Technical Report : Barriers to the Adoption of new Agricultural Technologies in Morocco: A systematic review - Boughlala, Mohamed; Dhehibi, Boubaker; Souissi, Asma; Moussadek, Rachid; Baum, Michael (2025)
This report examines the challenges and opportunities surrounding the adoption of new agricultural production technologies in Morocco, particularly within the cereal sector. Agriculture is an important component of the Moroccan economy, yet significant gaps exist between potential and actual yields. While the National Institute for Agronomic Research (INRA) has developed innovative practices in partnership with international organizations such as the International Center for Agricultural Research in the Dry Areas (ICARDA), adoption rates, especially among smallholders, remain low. This report explores the reasons behind this resistance, focusing on both the characteristics of the innovations themselves and the socio economic context in which farmers operate. The report highlights that while new technologies such as improved seed varieties, direct seeding, and optimized input applications offer proven benefits, various barriers hinder their widespread implementation. These include the high cost of technologies, particularly for small farms; limited access to credit; a lack of effective marketing channels for farmers; inadequate information dissemination and extension services; risk aversion among farmers; and the small size of many Moroccan farms. The report underscores that innovation is not purely technological but also requires the development of commercial strategies and supportive institutional frameworks, including state subsidies, and effective coordination between research, extension, and development services. Furthermore, it notes the importance of understanding farmers' perceptions, preferences, and constraints in order to facilitate the successful adoption of new techniques. The report also summarizes key literature on factors affecting agricultural technology adoption globally, including farm size, education, access to credit, and extension services, to identify research gaps specific to Morocco. It concludes that bridging the yield gap and ensuring sustainable agricultural practices in Morocco requires a holistic approach, considering technological, economic, social, and institutional factors.